2014
DOI: 10.1172/jci74565
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pandemic influenza immune memory signature after vaccination or infection

Abstract: The magnitude, quality, and maintenance of immunological memory after infection or vaccination must be considered for future design of effective influenza vaccines. In 2009, the influenza pandemic produced disease that ranged from mild to severe, even fatal, illness in infected healthy adults and led to vaccination of a portion of the population with the adjuvanted, inactivated influenza A(H1N1)pdm09 vaccine. Here, we have proposed a multiparameter quantitative and qualitative approach to comparing adaptive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…The results of our work demonstrate that serologic protection against influenza viruses can persists for many years. Consistent with other reports [27,28], our data suggest that past infections could protect a large part of the population throughout their lives.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our work demonstrate that serologic protection against influenza viruses can persists for many years. Consistent with other reports [27,28], our data suggest that past infections could protect a large part of the population throughout their lives.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, as in these recent studies, we detected an IFN-γ-mediated recall response in lymphocytes after stimulation with a cognate antigen. Other studies of distinct populations have also demonstrated that vaccination to infl uenza provides longterm immunity; however, these studies typically evaluated cell frequencies or the levels of cytokine production by certain cell types such as IFN-γ + IL-2 + cells, TNF-α CD4 + T cells, CD107 + CD8 + T cells, and IFN-γ + CD49 + CD8 + T cells stimulated in the presence of infl uenza peptide antigens (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry was performed as previously described [20]. To analyze influenza-specific T cells, PBMCs were stimulated overnight with inactivated A/H3N2 Wisconsin/67/2005 and A/H1N1/California/04/2009 in the presence of monensin/brefeldin A mix (Sigma).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…In addition to antibodies, T cell responses are also key parameters of influenza protection [20,[22][23][24][25][26]. We therefore analyzed the polyfunctional CD4 + and CD8 + T cell responses to inactivated whole virus (A/H1N1 and A/H3N2) in PBMC from our volunteer cohort at each time-point (Supporting information, Fig.…”
Section: Cellular Responses To Tivmentioning
confidence: 99%